2015
DOI: 10.1002/prop.201500087
|View full text |Cite
|
Sign up to set email alerts
|

10D massive type IIA supergravities as the uplift of parabolic M2‐brane torus bundles

Abstract: We remark that the two 10D massive deformations of the N=2 maximal type IIA supergravity (Romans and HLW supergravity) are associated to the low energy limit of the uplift to 10D of M2‐brane torus bundles with parabolic monodromy linearly and non‐linearly realized respectively. Romans supergravity corresponds to M2‐brane compactified on a twice‐punctured torus bundle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…We obtained its Hamiltonian and discussed its properties. The theory may be formulated on a bundle whose fiber is a punctured torus and whose structure group, the area preserving diffeomorphisms as suggested in [33]. By using the relationship between P M CG(Σ 1,2 ) and the (1, 1) − knots theory, we show that the monodromies associated with the twice punctured torus bundle are much richer than the ones associated with torus bundles without punctures.…”
Section: Jhep10(2021)212mentioning
confidence: 97%
See 2 more Smart Citations
“…We obtained its Hamiltonian and discussed its properties. The theory may be formulated on a bundle whose fiber is a punctured torus and whose structure group, the area preserving diffeomorphisms as suggested in [33]. By using the relationship between P M CG(Σ 1,2 ) and the (1, 1) − knots theory, we show that the monodromies associated with the twice punctured torus bundle are much richer than the ones associated with torus bundles without punctures.…”
Section: Jhep10(2021)212mentioning
confidence: 97%
“…The M2-brane with C ± fluxes compactified on M 9 × T 2 has the same properties. In [33] it was shown that only M2-brane torus bundles with parabolic monodromy (linearly or non-linearly realized) can be non-trivially uplift to M2-brane bundles on ten non-compact dimensions. The non-triviality of the M2-brane bundle is completely necessary to guarantee that the low energy limit of the decompactified M2-brane corresponds to any of the two massive type IIA supergravities in 10D (Romans and Howe-Lambert-West supergravity) and not to the massless case.…”
Section: The M2-brane With C − Fluxes and Monodromy In Sl(2 Z)mentioning
confidence: 99%
See 1 more Smart Citation
“…The Fermionic T-duality has also been studied for massive type IIA supergravity [41]. The relation between the massive IIA supergravity and M-theory has also been investigated [42]. A relation between massive IIA/IIB supergravities has also been analyzed, and it has been demonstrated that a duality exists between such massive supergravities [43]- [44].…”
Section: Introductionmentioning
confidence: 99%
“…Brane solutions associated with Type IIA massive supergravity were found in [6]. In [7] a M-theory origin proposal was made. Its uplift to eleven dimensions supergravity had been previously established in [8].…”
Section: Introductionmentioning
confidence: 99%